microRNA 146a ameliorates retinal damage in experimental autoimmune uveitis - Saraswathy, Sindhu; Rao, Narsing A. (Frontiers in Ophthalmology, 2023)
Uveitis and related intraocular inflammations are a major cause of blindness due to retinal damage caused by degeneration and loss of the photoreceptor cells. In mouse experimental autoimmune uveitis (EAU) we have shown mitochondrial oxidative stress with marked upregulation of αA crystallin in the inner segments of the photoreceptors. Such upregulation prevented apoptosis of photoreceptor cells and inflammatory cell infiltration. Furthermore, αA crystallin treatment prevented photoreceptor apoptosis from mitochondrial oxidative stress by suppressing innate and adaptive immunity in EAU. Since these immune processes are modulated by microRNAs, in this study we investigated (a) modulation of microRNAs during development of EAU by αA crystallin administration and (b) microRNA therapeutic intervention. Few microRNAs were significantly upregulated in EAU mice with intravenous injection of αA crystallin and among these, computational bioinformatic analysis revealed that the upregulated microRNA 146a targets the innate and adaptive immune responses. In EAU, intravenous administration of this microRNA prevented inflammatory cell infiltration in uvea and retina and preserved photoreceptor cells. This protective function was from suppression of the innate and adaptive immune responses and suggests that mir146a can be a novel therapeutic agent in preventing photoreceptor degeneration in uveitis.